2015
DOI: 10.1017/s0950268815002678
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological and clinical characteristics of severe fever with thrombocytopenia syndrome (SFTS) in China: an integrated data analysis

Abstract: Severe fever with thrombocytopenia syndrome (SFTS) is an emerging infectious disease that was caused by a novel bunyavirus, SFTSV. The study aimed to disclose the epidemiological and clinical characteristics of SFTSV infection in China so far. An integrated clinical database comprising 1920 SFTS patients was constructed by combining first-hand clinical information collected from SFTS sentinel hospitals (n = 1159) and extracted data (n = 761) from published literature. The considered variables comprised clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
61
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(68 citation statements)
references
References 26 publications
(35 reference statements)
1
61
4
Order By: Relevance
“…The overall CFR in our study was 32.6% which was compared with 12.2% reported recently in China [6]. Although the CFRs of consecutive three years has been decreasing, the CFRs may still be exaggerated.…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…The overall CFR in our study was 32.6% which was compared with 12.2% reported recently in China [6]. Although the CFRs of consecutive three years has been decreasing, the CFRs may still be exaggerated.…”
Section: Discussioncontrasting
confidence: 46%
“…The clinical manifestations of SFTS include fever, myalgia, vomiting, diarrhea, thrombocytopenia and leukopenia. In severe cases, multi-organ dysfunction may occur [5]; the case fatality ratio (CFR) has been reported to be 6.3–30% [6, 7]. …”
Section: Introductionmentioning
confidence: 99%
“…Though the fatality rate of SFTS in China has fallen from first reported 30% to present 12% owing to increased reporting, advances in diagnostic procedures and improved clinicians’ skills [5, 15, 16]. The risk factors for human infection with SFTSV were confirmed [15, 17] and national intervention programs were performed, including promoting public awareness, establishing sentinel hospitals and improving clinicians’ skills [2, 1820]. Yet, the number of fatal cases increases annually in China.…”
Section: Discussionmentioning
confidence: 99%
“…The national surveillance data from 2010 to 2013 in China showed that the incidence of SFTS and its epidemic areas are growing, but the case fatality rate (CFR) has steadily declined [1]. The major clinical symptoms of SFTS include fever, thrombocytopenia, leukocytopenia, gastrointestinal symptoms and various other systemic manifestations including muscular symptoms, neurological disorders and coagulopathy [2, 3]. Neurological symptoms were strongly associated with death, even though they occurred during the first week after disease onset [4].…”
Section: Introductionmentioning
confidence: 99%
“…Since SFTSV is a leading public health issues, researches on its clinical characteristics, pathogenic mechanism, detection methods, and epidemiologic characteristics were conducted (6)(7)(8)(9)(10)(11)(12)(13). With regards to SFTSV epidemiology, seroprevalence of the healthy population in endemic areas has previously been investigated (14)(15)(16); however, in non-endemic areas, it is unclear, and more knowledge in this area is urgently needed.…”
Section: Introductionmentioning
confidence: 99%